1988
DOI: 10.1111/j.1471-0528.1988.tb06479.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological prognostic indicators in cervical cancer with particular reference to patients under the age of 40 years

Abstract: Summary. The presence of lymph node metastases in patients with cervical cancer is an important predictor of death and recurrence of disease. Lymph node metastases are more common in patients with mucus‐secreting carcinomas than in women with pure squamous carcinomas even in what appears, clinically, to be early stage disease: such neoplasms are more frequent in women under the age of 40 years. The recognition of mucus secretion in a carcinoma and the detection of vascular permeation adjacent to the primary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…35 Our previous report revealed no difference between AC and ASC in the recurrence-free survival and overall survival; yet, ASC might relapse in distant sites more often than AC. 7 Diagnosis of ASC can be difficult when the tumor is poorly differentiated and predominantly squamous, or when glandular elements are identified using mucin stains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Our previous report revealed no difference between AC and ASC in the recurrence-free survival and overall survival; yet, ASC might relapse in distant sites more often than AC. 7 Diagnosis of ASC can be difficult when the tumor is poorly differentiated and predominantly squamous, or when glandular elements are identified using mucin stains.…”
Section: Discussionmentioning
confidence: 99%
“…7 Diagnosis of ASC can be difficult when the tumor is poorly differentiated and predominantly squamous, or when glandular elements are identified using mucin stains. 35 In our cases, a definite glandular differentiation must be seen for the diagnosis of ASC. All hematoxylin and eosin-stained slides contained both types of cells with the proportion of glandu- It is logical to think that patients having later stage diseases, bigger tumor size, higher grade tumors or at least patients having lymph node metastasis should have poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…7 A study reported that the average age with invasive cancer was 48 years. 8 We found that all patients were from the age group of 30 -60 years in the study group who received combined chemo radiotherapy and 26 patients in the control group were between the age group 61-80 years (chi-square = 8.26 df=2 p<.05) Study from Roswell Park, New York subsequently Kjorstad noted that in Norway during 1950 and 1960s the proportion of those less than 35 years old was only 7%. Hence age itself is an independent risk factor.…”
Section: Discussionmentioning
confidence: 70%
“…Colorações especiais para mucina, como o PAS com digestão, podem ser úteis na identifi cação dessa substância no componente glandular da lesão invasora ou no interior da lesão intra-epitelial (15,20) . Um sistema de classifi cação de tumores cervicais proposto por Fox incluiu a categoria dos carcinomas escamosos produtores de mucina -tumores com aspecto morfológico de carcinomas escamosos contendo mucina revelada por coloração especial (4) . Vários artigos destacaram a importância de se fazer o diagnóstico desses tumores, sugerindo que a coloração especial para muco seja realizada rotineiramente para detectá-los.…”
Section: Discussionunclassified